Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/ijc.25191
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of microRNAs and their targets are associated with acquired resistance of MCF‐7 breast cancer cells to cisplatin

Abstract: Cancer cells that develop resistance to chemotherapeutic agents are a major clinical obstacle in the successful treatment of breast cancer. Acquired cancer chemoresistance is a multifactorial phenomenon, involving various mechanisms and processes. Recent studies suggest that chemoresistance may be linked to drug-induced dysregulation of microRNA function. Furthermore, mounting evidence indicates the existence of similarities between drug-resistant and metastatic cancer cells in terms of resistance to apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
193
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(210 citation statements)
references
References 45 publications
11
193
1
3
Order By: Relevance
“…Our findings further indicate that inhibition of miR-181a in leukemia cells impacted their susceptibility to NKmediated lysis. Although emerging studies indicate the potential involvement of miR-146a in cell proliferation and drug resistance, 44,45 blocking miR-146a in our experimental model had no effect on NK-cell mediated lysis. Therefore, we hypothesized that miR-146a is involved in the molecular mechanisms that contribute to drug resistance but not to resistance to NK-mediated lysis.…”
Section: Discussioncontrasting
confidence: 60%
“…Our findings further indicate that inhibition of miR-181a in leukemia cells impacted their susceptibility to NKmediated lysis. Although emerging studies indicate the potential involvement of miR-146a in cell proliferation and drug resistance, 44,45 blocking miR-146a in our experimental model had no effect on NK-cell mediated lysis. Therefore, we hypothesized that miR-146a is involved in the molecular mechanisms that contribute to drug resistance but not to resistance to NK-mediated lysis.…”
Section: Discussioncontrasting
confidence: 60%
“…The exact role for the FOXP3-induced miRs identified in our study in normal and cancerous epithelial cells is yet to be determined, as each miR can potentially target multiple transcripts (Farazi et al, 2010). However, experimentally validated miR-7 targets including growth factor receptors and signalling molecules such as EGFR, PAK1, RAF-1, IRS1 and IRS2 are frequently upregulated in cancers (Kefas et al, 2008;Reddy et al, 2008;Pogribny et al, 2010), supporting a role for miR-7 in FOXP3 tumoursuppressor function. We have also observed the reduced mRNA levels for the miR-7 targets EGFR, PAK1 and RAF-1 in FOXP3-transduced BT549 cells correlating with the increased miR-7 levels (Supplementary Figure S8), suggesting that, in addition to suppressing SATB1, miR-7 may also suppress other important oncogenes.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, we reported that NCL has a critical protumorigenic function regulating the biogenesis of selected microRNAs (miRNAs), a class of noncoding single-stranded RNAs 19-22 nt in length (17) that regulate gene expression at the posttranscriptional level by targeting mRNAs in a sequence-specific manner (18). In fact, NCL enhances the maturation of specific miRNAs (including miR-21, miR-221, and miR-222) causally involved in cancer pathogenesis and resistance to several antineoplastic treatments (19)(20)(21)(22)(23). Our findings demonstrated that NCL modulates the biogenesis of these miRNAs at the posttranscriptional level, enhancing their maturation from pri-to premiRNAs, identifying a novel NCL-dependent oncogenic mechanism (19).…”
mentioning
confidence: 99%